Review OSINT tool for social engineering - Nobili, Martina (Frontiers in Big Data, 2023)
In recent years, we observed an increase in cyber threats, especially social engineering attacks. By social engineering, we mean a set of techniques and tools to collect information about a person or target to extort sensitive information. Such information might be used for (industrial) espionage, to blackmail the user, or represent the starting point to perform malicious cyber attacks against the individual or, more often, against the organization they work for. The human factor is often the most vulnerable element in the security of any system, and the mass of information we disseminate online largely facilitates social engineering activities. To prevent and mitigate social engineering attacks, Open Source INTelligence (OSINT) techniques and tools can be used to evaluate the level of exposition of an individual or an organization. OSINT is the collection of information through open sources, that is, sources not protected by copyright or privacy. The article reviews the main OSINT tools for countering and preventing social engineering attacks. Specifically, it proposes the different tools diving them accordingly to the specific information they allow to track (e-mail, social profiles, phone numbers, etc.).